The psychology of organizational change: new insights on the antecedents and consequences of individuals' responses to change - Oreg, Shaul; Michel, Alexandra; By, Rune Todnem (Cambridge University Press, 2023)
"The Psychology of Organizational Change is intended for academics, research students, and practitioners interested in understanding organizational change. The three audiences will be able to keep up to date on the most recent advances in the study of organizational change, focusing on the psychological aspects involved in change"--